2010
DOI: 10.1007/s10689-010-9408-8
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to chromosome 2q32.2-q33.3 in familial serrated neoplasia (Jass syndrome)

Abstract: Causative genetic variants have to date been identified for only a small proportion of familial colorectal cancer (CRC). While conditions such as Familial Adenomatous Polyposis and Lynch syndrome have well defined genetic causes, the search for variants underlying the remainder of familial CRC is plagued by genetic heterogeneity. The recent identification of families with a heritable predisposition to malignancies arising through the serrated pathway (familial serrated neoplasia or Jass syndrome) provides an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…12 Attempts to model the genetics of this syndrome as monogenic among unrelated individuals, or as Mendelian through linkage analyses, have not been successful. 13, 14 The genetic basis for this disorder remains undefined, with the exception that mutations in MUTYH have been observed in only a small minority of cases that present with concomitant tubular adenomas. 15 …”
Section: Background and Aimsmentioning
confidence: 99%
“…12 Attempts to model the genetics of this syndrome as monogenic among unrelated individuals, or as Mendelian through linkage analyses, have not been successful. 13, 14 The genetic basis for this disorder remains undefined, with the exception that mutations in MUTYH have been observed in only a small minority of cases that present with concomitant tubular adenomas. 15 …”
Section: Background and Aimsmentioning
confidence: 99%
“…In addition, multi-case families, with a predisposition to develop advanced serrated lesions (polyps and CRC) and a high frequency of CRC with the BRAF p.V600E mutation and variable levels of MSI (MSI-V), have been described(16). In a study of 11 such families, we have shown that 7 demonstrated linkage to the same region of chromosome 2q32.2-q35 (15) supporting a genetic predisposition to develop serrated neoplasia.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to its occurrence in CRCs from individuals with no family history of CRC (7), the BRAF p.V600E mutation is frequently observed in the CRCs from multiple relatives within families with serrated neoplasia predispositions such as Jass syndrome (15, 16) and serrated polyposis(17). Previous studies have demonstrated a positive association of family history of both CRC and extracolonic cancers (ECCs) with risk of a BRAF -mutated CRC (11, 18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Although biallelic MutYH mutations have been reported in some individuals meeting WHO criteria for serrated polyposis, 50 clinical genetic testing in these patients has been low yield. Studies in individual families have reported linkage to loci on chromosomes 1p 51 and 2q 52 ; however no definitive candidate genes have been identified.…”
Section: Familial Crc Without Identifiable Gene Mutationsmentioning
confidence: 99%